River Water Purifier as an Alternative for Clean Water Supply in Sei Siarti Village, Panai Tengah District, Labuhanbatu Regency - Hasibuan, Azhari; Nasution, Tulus Ikhsan; Sujatmoko, Koko; Dewinta, Astrid Fauzia (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Sei Siarti Village, Panai Tengah District, Labuhanbatu Regency have problems in the form of limited clean water sources that are suitable for use. There are several potentials including peat water, drilled well water, and Barumun river water that crosses the village. The condition of peat water that does not comply with quality standards for water that is fit for consumption has a brownish color, high acidity, and the organic matter contained in peat water is high enough to cause an odor. The well water has a salty taste (high salt content) so that what has the potential is Barumun river water even though it has a cloudy color. The method used to purify cloudy river water is through the processes of coagulation (deposition), filtration (filtering), absorption (absorption), and adsorption (ion exchange). This water purifier is made using 2 tubes filled with silica sand, MGS, activated carbon, and zeolite sand so that the water produced is clear and fit for consumption and can be utilized by the surrounding community. The results obtained from this water purification are water that does not have a smell, taste, and is clear in color so that it is suitable for use by the surrounding community